Cross-dehydrogenative coupling involving benzylic and allylic C–H bonds. Issue 13 (1st June 2020) - Bosque, Irene; Chinchilla, Rafael; Gonzalez-Gomez, Jose C.; Guijarro, David; Alonso, Francisco
Abstract : Benzylic and allylic C–H bonds are coupled with C(sp)–H, C(sp 2 )–H and C(sp 3 )–H bonds in a straightforward and high atom-economic manner. Abstract : In recent years, the cross-dehydrogenative coupling (CDC) has demonstrated to be a powerful synthetic tool to form C–C bonds from two C–H bonds. This high atom-economic transformation is an attractive alternative to the classical substitution and coupling approaches for the benzylation and allylation of carbon centers, which rely on the reaction of adequately functionalized starting materials. This review emphasizes the utility of the CDC through the coupling of benzylic and allylic C–H bonds with C(sp)–H, C(sp 2 )–H and C(sp 3 )–H bonds.